2000
DOI: 10.1097/00000539-200005000-00038
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Hemodynamic Changes After Endotracheal Intubation by Using the Lightwand Device and the Laryngoscope in Normotensive and Hypertensive Patients

Abstract: We compared the effects of the lightwand technique on hemodynamic responses, time-to-intubation, number of attempts, and complications during tracheal intubation with those of direct-vision laryngoscopy in normotensive (LN and TN group; n = 20, respectively) and hypertensive (LH and TH group; n = 20, respectively) patients. Lightwand or laryngoscopic oral endotracheal intubation was performed after the induction of anesthesia with fentanyl and propofol and muscle relaxation with vecuronium. Systolic blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 4 publications
2
42
1
1
Order By: Relevance
“…Similar investigations using a lightwand (Trachlight™, Laerdal Medical, Armonk, NY, USA) technique have been conducted, 9,10 since this method of intubation requires neither elevation of the epiglottis by the laryngoscope blade nor exposure of the glottic opening. However, both Hirabayashi et al 9 and Nishikawa et al 10 found that the circulatory responses to tracheal intubation were similar to those of direct-vision laryngoscopy. Hirabayashi et al 9 used a jaw-lifting technique for lightwand intubation, and they speculated that the magnitude of this stimulus was sufficient to cause a circulatory response.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar investigations using a lightwand (Trachlight™, Laerdal Medical, Armonk, NY, USA) technique have been conducted, 9,10 since this method of intubation requires neither elevation of the epiglottis by the laryngoscope blade nor exposure of the glottic opening. However, both Hirabayashi et al 9 and Nishikawa et al 10 found that the circulatory responses to tracheal intubation were similar to those of direct-vision laryngoscopy. Hirabayashi et al 9 used a jaw-lifting technique for lightwand intubation, and they speculated that the magnitude of this stimulus was sufficient to cause a circulatory response.…”
Section: Resultsmentioning
confidence: 95%
“…Hirabayashi et al 9 used a jaw-lifting technique for lightwand intubation, and they speculated that the magnitude of this stimulus was sufficient to cause a circulatory response. 9 Nishikawa et al 10 required significantly more time for intubation and a greater number of attempts at intubation using the lightwand technique, compared to laryngoscopy. The technique employed in our study required only a short period of time and no jaw lifting for intubation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] In the present study, we used lightwand-assisted and fibreoptic intu- values are expressed as mean ± SD. MAP=mean arterial pressure; HR=heart rate; RPP=rate-pressure product; F=patients without hypertension (q) and with hypertension (n) itubated with a fibreoptic endoscope; L=patients without hypertension (q) and with hypertension (n) intubated with a lightwand.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Fibreoptic endotracheal intubation, which requires neither elevation of the epiglottis nor exposure of the glottis by a laryngoscope blade, requires skill in manipulation of the endoscope. 6 On the other hand, a lighted stylet also enables intubation to be performed without the use of laryngoscope.…”
mentioning
confidence: 99%